Pollutants In the Selected 3 – Bus Station Microenvironments in Enugu Metropolis (International Journal of Scientific Research in Science and Technology, 2024)
Idling buses in bus station micro-environments potentially pollute ambient air with health implications for commuters with long waiting times. This study aimed at finding the severity of air pollutants in selected three bus station microenvironments in Enugu metropolis, South Eastern Nigeria with the objective to determine the air quality index. Real time measurements of ambient particulates (PM10 and PM2.5) and gaseous pollutants such as SO2, NO2 and CO were monitored, in conjunction with meteorological parameters (wind speed, temperature and relative humidity) on idling buses in selected three bus stations and a control station in Enugu Metropolis. The study spanned through September 2016 to August 2018, covering dry and wet seasons. Hand-held Aeroqual Series - 200 gas monitor/sensors, particulates laser meter and ambient weather anemometer were used to collect data. Results indicated that the daily highest mean concentrations of pollutants were as follows: PM10=228µg/m3 – Young Shall Grow; PM2.5=99.5µg/m3 – Young-Shall-Grow; SO2=0.81ppm – Ifesinachi; NO2= 0.068ppm – Young-Shall-Grow; CO= 7.376ppm – ABC, consistently maintained higher concentrations than those at the control station. AQI was calculated with AQI calculator. The air quality index (AQI) results showed a severe health issue in the selected 3-bus station micro environments. This implies that commuters are highly at risk if they cluster idling buses at bus stations. This study can assist the relevant authorities to set strict ambient air quality objectives for pollutants in transport micro environments.
Keywords: AQI; Idling; Particulates; Gaseous Pollutants; Micro Environment; Severity